EVALUATION OF THE COLLECTIVE EFFICACY OF TREATMENT COMBINATIONS IN MANAGING METASTATIC BREAST CANCER USING META-ANALYSIS - Omole , O.O; Oniyinde , Y.O; Mustapha , T; Audi , N.I. (International Journal of Allied Sciences (IJAS), 2025)
The motivation for meta-analysis of the effect of the collective treatment combination for metastatic breast cancer is to provide a more comprehensive and accurate estimate of the effect on survival rates and adverse reactions. Survival rates are an important outcome measure in the treatment of metastatic breast cancer, and several studies have been investigated. This paper aimed to evaluate the collective efficacy of treatment combinations in managing metastatic breast cancer using meta-analysis. The effect size index was hazard ratio, dateset was sourced via published date in a reputable journal. The random-effects model was employed for the analysis. The studies in the analysis were assumed to be random sample from a universe of breast cancer studies. The summary effect size was 2.545 with a 95% confidence interval of 1.988 to 3.260, The Z-value tests the null hypothesis that the mean effect size is 1.000. The Z-value is 7.405 with p < 0.001. Using a criterion alpha of 0.050, we can reject this null hypothesis. The Q-value is 68.921 with 10 degrees of freedom (k-1), I-squared statistic was 92%. This study recommends that personalized treatment plans based on individual patient profiles should be prioritized